Information needs and usage among undergraduate medical students of Universiti Teknologi Mara / Shahrani Abdul Manaf - Abdul Manaf, Shahrani (2013)
The study highlighted the purpose of students’ information needs, frequency in consulting the resources, evaluation criteria in finding and using information sources and difficulties faced in meeting information needs. The aim of the study is to investigate the information needs and usage among undergraduate medical students of Universiti Teknologi MARA and to find out the relationship between use of information, students’ year of study and information skills as well as. There are specific questions that guide the research: 1) What are the information needs and usage of the students?; 2) What are the criteria of evaluation in finding and using the information sources?; and 3) What are the difficulties faced in searching and using information? The study applied a quantitative research approach with a 240 respondents of students. The findings prove that the students’ level of study has significant relationship between the frequencies of information resources consulted, the criteria of evaluation in searching and using the information sources, the difficulties faced, frequencies in searching information in the library, and amount of time spend to find information in the library. Besides that, the findings also prove that information skills class/library instruction session has significant relationship between the frequencies of information resources consulted, the criteria of evaluation in searching and using the information sources, difficulties faced, and frequencies in searching information in the library. There are several significance of this study which is a guideline for the future implementation of strategies in improving the level of undergraduate students’ information literacy towards utilisation the variety of information sources and as a measurement tools in enhancing students’ competences for locating, selecting, evaluating and using information essential for lifelong learning. It should start the initiation of a dialog among faculty, students and librarians about the information use on the campuses. All this thing should be addressed through policy, training, curriculum development and most importantly, working together toward a solution with campus stakeholders, including librarians, students and faculty.